2006
DOI: 10.13182/nse05-64
|View full text |Cite
|
Sign up to set email alerts
|

Neutron Capture and Total Cross-Section Measurements and Resonance Parameters of Gadolinium

Abstract: -Neutron capture and transmission measurements were performed by the time-of-flight tech

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(61 citation statements)
references
References 18 publications
2
54
0
Order By: Relevance
“…Again, the Gd cross sections have been revised after the present calculations were made, which may change the calculated neutron spectrum and thereby change partially the results for Gd pins. 18) Larger deviations have also been highlighted for HELIOS1.6 (up to 4.1%), essentially close to the Hf-vertex.…”
Section: U-capture Rate (C 8 ) Distributionmentioning
confidence: 81%
See 2 more Smart Citations
“…Again, the Gd cross sections have been revised after the present calculations were made, which may change the calculated neutron spectrum and thereby change partially the results for Gd pins. 18) Larger deviations have also been highlighted for HELIOS1.6 (up to 4.1%), essentially close to the Hf-vertex.…”
Section: U-capture Rate (C 8 ) Distributionmentioning
confidence: 81%
“…Recently, it has been found that the revised data for the cross sections for Gd isotopes may alter the latter conclusion. 18) Finally, certain additional sensitivity studies have been presented. These have shed light on some of the possible causes of the observed discrepancies and have, in particular, underlined the importance of an accurate representation of the control blade position.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A set of resonance parameters for gadolinium up to 300 eV as well as a more detailed description of the present measurements is available in References [2,3]. Twenty-eight resonances were introduced that were not included in ENDF.…”
Section: Epithermal Resultsmentioning
confidence: 99%
“…The effort was optimized by the use of isotopically-enriched samples, diluted liquid samples, combined transmission and capture measurements, and Bayesian analysis using the SAMMY [1] computer program. A detailed description of these measurements and analyses is given in References [2,3]. Gadolinium has the highest thermal cross section of any natural element.…”
Section: Introductionmentioning
confidence: 99%